Market Segmentation of Clients of Brick&Mortar Pharmacies when Buying OTC Drugs - Lošťáková, Hana; Příhodová, Markéta (STEF92 Technology Ltd., 2016)
The aim of this article is to summarize the results of a primary quantitative research focused on preferences and buying behavior of clients of B&M pharmacies when buying OTC drugs and dietary supplements, and the segmentation of the market, including the profile characterization of individual market segments. The research was conducted in 2016 by the University of Pardubice using personal interviews in households in the East Bohemian region selected by multistage random sampling. The research has proven that clients of B&M pharmacies differ in their preferences and shopping behavior. They can be divided into five market segments - price-sensitive, looking for quality at a reasonable price, less demanding, rushing and demanding. The article specifies profiles of these segments.
Segmentace trhu klientů kamenných lékáren při nákupu volně prodejných léků
Keywords: pharmaceutical market; OTC drugs; dietary supplements; market segmentation; B&M pharmacies; farmaceutický trh; volně prodejné léky; doplňky stravy; segmentace trhu; kamenné lékarny